ANALISIS PENERIMAAN MAHASISWA UPH TERHADAP UPH MOODLE LEARNING MANAGEMENT SYSTEM MENGGUNAKAN METODE TAM - Agustina Christiani; Anabella Karlinda (Jurnal Ilmiah Teknik Industri, 2023)
Utilization of an information technology, in this case the LMS at UPH, namely Moodle, can be done effectively if students as users have the competence to use it. Moodle has been used at UPH since before the Covid-19 pandemic and the pandemic became the catalyst for using Moodle. Meanwhile, it is known that no research has been conducted on UPH’s student acceptance of Moodle. Therefore, a study was conducted to analyze the factors influencing UPH’s student acceptance of UPH Moodle LMS using the TAM. TAM is a model of acceptance of information technology, which consists of 5 variables: perceived ease of use (PEOU), perceived usefulness (PU), attitude to use (ATU), behavior to continue using (BIU), and real use (AU). To test hypotheses, a questionnaire was prepared and distributed to active students of the UPH Lippo Village regular undergraduate program batches of 2020, 2021, and 2022. The total number of respondents who filled in was 257 respondents and data was sorted so that the total data used was 178 respondents. Data processing uses SEM-PLS with SmartPLS software. The results of this study are 6 hypotheses accepted and 1 hypothesis rejected, which are PEOU has a positive and significant effect on PU and ATU, PU has a positive and significant effect on ATU and BIU, ATU has a positive and significant effect on BIU, BIU has a positive and significant effect on AU, PU does not has a positive and significant effect on AU.